2017
DOI: 10.1002/advs.201700567
|View full text |Cite
|
Sign up to set email alerts
|

Verifying the Rechargeability of Li‐CO2 Batteries on Working Cathodes of Ni Nanoparticles Highly Dispersed on N‐Doped Graphene

Abstract: Li‐CO2 batteries could skillfully combine the reduction of “greenhouse effect” with energy storage systems. However, Li‐CO2 batteries still suffer from unsatisfactory electrochemical performances and their rechargeability is challenged. Here, it is reported that a composite of Ni nanoparticles highly dispersed on N‐doped graphene (Ni‐NG) with 3D porous structure, exhibits a superior discharge capacity of 17 625 mA h g−1, as the air cathode for Li‐CO2 batteries. The batteries with these highly efficient cathode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
116
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 39 publications
(14 reference statements)
3
116
1
Order By: Relevance
“…Figure 1d shows the XRD patterns of the as-prepared Ni@N-Cc omplex. [40,44] Electrochemical characterization of the Ni@N-C complex The content of Ni wasa sl ow as only 1.42 AE 0.65 at %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1d shows the XRD patterns of the as-prepared Ni@N-Cc omplex. [40,44] Electrochemical characterization of the Ni@N-C complex The content of Ni wasa sl ow as only 1.42 AE 0.65 at %.…”
Section: Resultsmentioning
confidence: 99%
“…[43] In addition, the de-convoluted C1ss pectrum can be fitted with three different types of carbon species in CÀC( 284.6 eV), CÀN( 285.8 eV), and C=O ( Figure S3;288.2 eV). [40,44] Electrochemical characterization of the Ni@N-C complex…”
Section: Resultsmentioning
confidence: 99%
“…[ 63] This work is instructive for developing highly efficient nonprecious metal cathodes for Li-CO 2 www.advsustainsys.com the conductive matrix (Mo 2 C/CNTs) prepared by a carbothermal reduction process. [64] They found that the Mo 2 C nanoparticles could stabilize the Li 2 C 2 O 4 intermediate reduction product of CO 2 on discharge and prevent its disproportionation to Li 2 CO 3 .…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…Furthermore, the reversible hybrid aqueous LiÀCO 2 battery showed superbr ate performance even at high currentd ensities. These advantages of the reversible hybrid aqueous LiÀCO 2 battery could be duet ot he new reaction mechanism derived from the integration of aL ia node and aqueous catholyte in the battery.I nr eported organic LiÀCO 2 batteries, the battery reaction mostly occurs as described in Equation (1): [21] Figure 2. The discharge voltage and HCOOH production of the reversible hybrid aqueousLi ÀCO 2 battery.a )Galvanostaticd ischarge voltagesa nd b) the corresponding FEsofH COOH and H 2 at different currents.c )Galvanostatic long-termdischarge curve at 5.56 mA cm À2 and corresponding product selectivity.…”
Section: Resultsmentioning
confidence: 99%